Regional inequality in Türkiye: a new determination method - Sakarya, Adem (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2026)
Regional inequality remains a critical issue globally and locally, with various methods used to measure it. This study introduces a new approach using weighted mean centers (WMCs) of gross domestic product (GDP) and population to assess inequality and its changes. Overlapping WMCs indicate equality, divergence signals increasing inequality and convergence suggests decreasing inequality. The study analyzes T & uuml;rkiye's provincial-level inequality in five-year intervals from 2005 to 2020. It also examines WMCs for the agriculture, industry and service sectors to evaluate sectoral inequality. Findings confirm the existence of regional inequality in T & uuml;rkiye. While inequality has generally declined, trends vary based on macroeconomic conditions, increasing during growth periods and decreasing during economic shrinkage. Sectoral analysis reveals significant inequality in industry and services, though industrial inequality showed the most decline. The service and industrial sectors make up a large portion of the GDP, especially industry, and their agglomeration in certain provinces, as well as their unbalanced distribution across the country, explain the inequality. These results show that the policies aimed at reducing inequality both as a whole and at the regional level need to be revised.
Keywords: Regional inequality; weighted mean center; gross domestic product; population; T & uuml; rkiye; POLICIES; GLOBALIZATION; DISPARITY; CLUSTERS; TURKEY; Environmental Sciences & Ecology; Geography; Public Administration; Urban Studies